Battery Usage Monitoring System Internet of Things-Based Electric Cars (IoT) and Radio Telemetry - Hasibuan, Ahmad Firdaus; Ma’arif , Alfian (Universitas Ahmad Dahlan, 2024)
Making electric cars at Ahmad Dahlan University has started since 2019. The implementers in making this electric car are students from the Faculty of Teacher Training and Education, Automotive Technology Vocational Education Study Program and Faculty of Industrial Technology, Electrical Engineering Study Program which started by taking part in a Comparative Study at a Contest Indonesian Electric Car 2019. 2019 at Bandung State Polytechnic. The IoT and Radio Telemetry Based Electric Car Energy Usage Monitoring System created by researchers uses voltage sensor components and current sensors to detect voltage and current in electric cars, NodeMCU ESP32 as a microcontroller, voltage sensors to detect voltage, current sensors to detect current in car electricity and LCD as a reading output from the sensor. Also using IoT ThingSpeak as a display of sent sensor readings requires an internet connection to the microcontroller and radio telemetry as a display of sensor data on a serial monitor without requiring an internet connection. As a result, the tool created can monitor voltage and current accurately from a distance as long as it is connected to the internet and not connected to the internet. The best parameters obtained are the voltage and current sensors because the difference in reading error values from the sensor to the device does not reach 2, therefore they are the best parameters for this monitoring system.